Improvement of motivation environment in Russian innovation-oriented companies - A. V. SAYAPIN (Real Economics Publishing House, 2017)
The article represents main terms of motivation environment concept, elaborated by the author, as an instrument for personnel involvement growth in a company’s innovation process. Analysis of motivation environment components in Russian high-tech innovation-oriented companies “AO «NPO “Krypten»” and “OOO «Verilion»” is held, and problem aspects, which prevent to the companies' effective activity are defined. Practical instruments and recommendations for their solution are offered. Positive influence of motivation environment in a process of commercial organisations' strategic development is proved.